Theory of public finance in a federal state - Wellisch, Dietmar (Cambridge University Press, 2000)
"The last few decades have seen a substantial increase in the mobility of capital and population between the individual jurisdictions of long-established federal states (such as Canada, Germany, and the United States) and among the formerly independent member countries of the European Union. This book examines the consequences of this development for government policy. Its central question is whether the assignment of government functions to the individual jurisdictions in a federal state can ensure an optimal allocation of resources and a fair distribution of income."--Jacket